Quality of working life and career engagement among young cancer survivors in Malaysia - Hamzah, Siti Raba'ah; Muda, Zulaiha; Musa, Siti Nur Syuhada (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Careers today increasingly require engagement in proactive career behaviors; however, there is a lack of validated measures assessing among young adults cancer survivors in Malaysia. The purpose of this study was to investigate the relationship between quality of work life and career engagement among young adult cancer survivors in Malaysia. A cross sectional study was conducted among 400 young adults cancer survivors in Malaysia, between July 2019 until September 2018 with the young adult cancer survivors aged 18 – 40 years old, Malaysian citizens and having follow-up session at Hospital Kuala Lumpur and National Cancer Institute Malaysia. Qualities of work life and career engagement variables were determined from surveys and validated instruments. Correlation methods were performed to investigate the relationships among the variables. More than half of young adults cancer survivors were female 227 (56.8%) and male 173 (43.3%). They are Malays 292 (73%), Chinese 71 (17.8%) and India 37 (9.3%). The study found that the level of quality of work life (M=4.26, SD=0.532) and career engagement (M=4.23, SD=0.607) were high on a scale of 5 among young adult cancer survivors in Malaysia. Statistically significant and positive associations were found between career engagement (r =.746, p=.000) with the quality of work life among them. Next, the R-squared of 0.557 implies that the career engagement explain about 56% of the variance in the quality of work life. The results of the present study indicate that the career engagement associated with quality of work life. High quality of work life can give a result in better organizational performance. It is likely that tailored interventions targeting on these factors may support greater employment quality for young cancer survivors.